UPACARA RAMBU SOLO’ DI KELURAHAN PADANGIRING KECAMATAN RANTETAYO KABUPATEN TANA TORAJA - Naomi, Resanti; Matheosz, Jenny Nelly; Deeng, Djefry (Universitas Sam Ratulangi, 2020)
The ceremony is an act or celebration which is carried out or carried out as an important event, in its implementation it contains various rules that must be obeyed by indigenous peoples. Which rules grow and develop automatically and hereditary with the role of preserving order and peace of life of its supporters. As is the case with the Toraja people, who until now still carry out the solo sign ceremony 'as a reminder of the affection of the dead during their lives for the family or relatives left behind. So it is undeniable that the family or relatives of the dead try as much as possible for the implementation of a solo sign 'In the Toraja community if a rambu solo ceremony has not been carried out' then the deceased person is still considered a sick person, because of the importance of carrying out the ceremony.Keywords: ceremony, rambu solo', Toraja